Labor Market Effects of Short-Cycle Higher Education Programs : Challenges and Evidence from Colombia - Ferreyra, Maria Marta; Galindo, Camila; Urzúa, Sergio (World Bank, Washington, DC, 2021)
This paper estimates the labor market effects of enrolling in a short-cycle program in Colombia. Following evidence for the U.S., increasing access to short-cycle degrees might attract some students who would not have enrolled in higher education otherwise (i.e., the expansion or democratization margin), while also inducing other students to divert from bachelor's- and into short-cycle- degrees (i.e., the diversion margin). To identify responses along these margins, this paper uses an Instrumental Variables strategy and exploits local variation in the supply of short-cycle programs for the universe of high school graduates in 2005. Having at least one higher education institution specialized in short-cycle degrees within a 10 km radius of the student’s high school municipality increases enrollment in short-cycle programs by 3 percentage points, or 30 percent of the sample average. Results indicate that this enrollment increase is largely driven by students who would divert from bachelor's to short-cycle degrees due to changes in the local supply of short-cycle program. For these students, SCPs improve participation in the formal labor market among females, although they lead to lower monthly wages among males.